2014
DOI: 10.1155/2014/648294
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Rifampicin and Isoniazid Resistant Mycobacterium tuberculosis Using Genotype MTBDRplus Assay in Nepal

Abstract: Rapid line probe assay (LPA) can be a practical and rapid alternative to the slow conventional phenotypic drug susceptibility testing (DST) for detection of drug resistant tuberculosis (TB). The purpose of this study is to determine the diagnostic accuracy of Genotype MTBDRplus, LPA for TB, and compare its performance with conventional DST. A total of 54 culture samples were analyzed for DST using both conventional proportion method and MTBDRplus, where conventional DST identified 43 isolates (79.6%) as drug r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 22 publications
3
14
3
Order By: Relevance
“…For the GenoType MTBDRplus assay, previous studies have reported the sensitivity, specificity, PPV and NPV values in detecting INH resistance as ranging between 60%-100%, 95.1%-100%, 97.4%-100% and 90.7%-100%, respectively. In addition, this assay's sensitivity, specificity, PPV and NPV values in detecting RIF resistance are in the range of 82.3%-100%, 73.2%-100%, 81%-100% and 98.9%-100%, respectively [16][17][18][19][20][21][22][23][24][25]. When the results were evaluated, this assay seemed to be more sensitive for detecting RIF resistance than INH resistance.…”
Section: Resultsmentioning
confidence: 95%
“…For the GenoType MTBDRplus assay, previous studies have reported the sensitivity, specificity, PPV and NPV values in detecting INH resistance as ranging between 60%-100%, 95.1%-100%, 97.4%-100% and 90.7%-100%, respectively. In addition, this assay's sensitivity, specificity, PPV and NPV values in detecting RIF resistance are in the range of 82.3%-100%, 73.2%-100%, 81%-100% and 98.9%-100%, respectively [16][17][18][19][20][21][22][23][24][25]. When the results were evaluated, this assay seemed to be more sensitive for detecting RIF resistance than INH resistance.…”
Section: Resultsmentioning
confidence: 95%
“…Genomic DNA of Mycobacterial culture was extracted by incubating the colonies dissolved in 300 μ L of molecular biology grade water for 20 minutes at 95°C in water bath followed by 15 minutes in ultrasonic bath and centrifugation for 5 minutes at 12000 rpm [ 2 ]. Polymerase chain reaction (PCR) and hybridization were performed following manufacturer's recommendations (Hain Lifescience, Nehren, Germany) [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tuberculosis is a serious public health problem mainly in developing countries [ 1 ]. More than 95% of the tuberculosis cases and deaths related to tuberculosis occur in poorer countries [ 2 ]. Further, the multidrug-resistant tuberculosis is emerging as a serious threat to tuberculosis control programs in developing countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations